EFFECT OF BAKING MODES AND OPTIONSIN A STEAM-CONVECTION OVEN ON QUALITY OF BUNS - Davydenko N.I.; Urzhumova A.I.; Sheveleva G.I.; Grigor'eva R.Z. (Техника и технология пищевых производств)
In recent years much attention is paid to the catering service in the socially significant establishments of public catering. As part of a number of federal programs, re-equipment of kitchens and updating of the product assortment are carried out. Firstly, the re-equipment in the kitchens includes installation of modern thermal equipment such as a steam-convection oven. A steam- convection oven is a versatile equipment used for baking as well. The objective is to study the effect of modes and options of baking in the steam-convection oven on the formation of quality buns at socially important establishments of public catering (exemplified by school meals). At different stages of the research work the objects were: wheat flour by two manufacturers occupying a significant share of the region's flour market; semi-finished and finished bakery products. The quality of raw materials and finished products were evaluated with the standard methods by combinated organoleptic and physico-chemical parameters. It was found that the differences in the quality of flour samples studied did not significantly affect the quality of buns, baked in a catering establishment. It is shown that when baked in a steam-convection oven at the convection mode and at the temperature specified in the recipe books, the products have defects that reduce the quality of the products. The best quality factor and the lowest baking losses were possessed by products baked in a steam-convection oven with the steam and convection ratio of 20-30% and 70-80%, respectively. In each case the duration of baking should be determined individually, based on the weight of dough pieces, the shape and the desired surface color.